Application of thermal treatment for various cocos nucifera samples to the sucrose content analysis - Siti Noredyani, Abdul Rahman (2009)
The percentage of diabetics has shown unwelcomed increment recently and one of the methods to mitigate this situation is by increasing the production of Fructo-Oligosaccarides (FOS) in the market. FOS is very useful product for diabetics as it can reduce the amount of sugar in their blood. Sucrose which can be found in coconut samples is the raw material to produce FOS. Through thermal treatment of the coconut samples, the percentages of sucrose production can be determined. In this research, three types of coconut samples being used which are coconut water (22.41% sucrose content), coconut sugar A (17.88% sucrose content) and coconut sugar B (14.95% sucrose content). The thermal treatment involves specific procedures of heating and cooling which can give effects to the microstructures of each sample. Two parameters has been analyzed in this study which are temperature and exposure time. The changes of sucrose concentration in each sample have been analyzed using UV-Vis Spectrometer. The experimental results show that increased in temperature and exposure time resulted in increased of sucrose concentration. Optimal conditions for coconut water are 181.64 minutes exposure time and 70oC with the concentration of sucrose produced is 343.53 g/L. Without the thermal treatment, the concentration of sucrose is only 224.05 g/L or 34.78% lower than with thermal treatment. Meanwhile, optimal conditions for coconut sugar A and coconut sugar B are 199.24 minutes and 202.08 minutes respectively, both at temperature of 70oC. At these optimal conditions, coconut sugar A produced 398.06 g/L of sucrose (55.08% higher than without thermal treatment) and coconut sugar B produced 305.37 g/L of sucrose (51.04% higher than without thermal treatment). In conclusion, after performing the thermal treatment for the three types of coconut samples, coconut sugar A is the best sample where the production percentage of sucrose has been increased up to 55.08% after 199.24 minutes exposure time at 70oC.